2017
DOI: 10.1111/hepr.12857
|View full text |Cite
|
Sign up to set email alerts
|

Development of a simple predictive model for decreased skeletal muscle mass in patients with compensated chronic liver disease

Abstract: The BALB scoring system based on routinely used clinical parameters offers a convenient and non-invasive method for predicting DSMM in compensated CLD patients with high accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
1
14
3
Order By: Relevance
“…Therefore, the serum BTR is considered to more strongly reflect the state of increased energy consumption within skeletal muscles, especially in athletes. In contrast to the correlations found in the present study, circulating BCAA levels have been reported to decrease with the decreases in skeletal muscle mass in patients with chronic liver diseases [8] and chronic heart failure [7]. In those studies, the diseases may have led to increased BCAA catabolism or insufficient BCAA intake, resulting in decreased concentrations of circulating BCAAs, which in turn may lead to a reduction in skeletal muscle mass.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, the serum BTR is considered to more strongly reflect the state of increased energy consumption within skeletal muscles, especially in athletes. In contrast to the correlations found in the present study, circulating BCAA levels have been reported to decrease with the decreases in skeletal muscle mass in patients with chronic liver diseases [8] and chronic heart failure [7]. In those studies, the diseases may have led to increased BCAA catabolism or insufficient BCAA intake, resulting in decreased concentrations of circulating BCAAs, which in turn may lead to a reduction in skeletal muscle mass.…”
Section: Discussioncontrasting
confidence: 99%
“…Sarcopenia (i.e., a decrease in skeletal muscle mass) is a serious clinical problem associated with poorer prognosis in various diseases [5,6]. Studies have reported a relationship between skeletal muscle mass and the concentration of circulating BCAAs in several diseases [7,8]. Patients with chronic heart failure showed lower serum BCAA concentrations and Fisher's ratios than controls, with positive correlations between the values of their skeletal muscle index (SMI), defined as skeletal muscle mass divided by the squared height, and their BCAA concentrations and Fisher's ratios [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age ( P < 0.001) was significantly higher in patients with sarcopenia than in those without sarcopenia. In contrast, the mean body mass index (BMI), which is reported to be associated with loss of skeletal muscle mass, and serum BCAA levels were markedly lower in patients with sarcopenia than in those without sarcopenia ( P < 0.01).…”
Section: Resultsmentioning
confidence: 96%
“…Mac-2 binding protein glycosylation isomer (M2BPGi) as a liver fibrosis marker was tested, as reported elsewhere [26]. Skeletal muscle index (SMI, kg/m 2 ) was tested using BIA, as reported elsewhere [27]. SMI decline was defined as <7.0 kg/m 2 in males and < 5.7 kg/m 2 in females, referring to the Japanese guidelines [10].…”
Section: Patientsmentioning
confidence: 99%